Kendala Pelaksanaan Vaksinasi Covid-19 di Kecamatan Lintau Buo - Silvia Sukma Sari (Policy, Law and Political Research Center, 2022)
This study aims to find out how the implementation of the Covid-19 vaccination that occurred in Lintau Buo District. This type of research is a quasi-qualitative research using simple research methods, the withdrawal of informants using purposive sampling technique. Thus the data collection was carried out by means of interviews, observation and documentation studies. Data analysis was carried out by reducing data, presenting data and drawing conclusions. Then the validity of this data was tested by triangulation of sources and then analyzed. Based on the findings, it can be concluded that the obstacles that occur in the implementation of the Covid-19 vaccination in Lintau Buo District are divided into 2 internal and external obstacles. An internal obstacle in the implementation of stages 1 to 4 is the limited availability of vaccines. Human resources in implementing agents are not yet optimal. In the implementation of the implementation, the Population Identification Number of the community was not found so they had to report to the Dukcapil first. In addition, the cold chain capacity is insufficient for vaccine storage. Meanwhile, the external constraints at the launch stage of stages 1 to 4 came from the implementation targets. Lack of public awareness of Lintau Buo regarding the implementation of the Covid-19 vaccination. Many people only complete the first dose without completing the second dose on the grounds that they have already received the first certificate.